Cortical Gyrification in Methamphetamine Associated Psychosis: A Potential Neurodevelopmental Biomarker for Risk of Psychosis - Gribble, Amy (Department of Psychology, 2025)
For many years, methamphetamine associated psychosis (MAP) has been viewed as a symptomatic, genetic, and morphological blueprint for schizophrenia spectrum disorders (SSD) (Aoki et al., 2013; Grant et al., 2012; Uhlmann et al., 2016; Yang et al., 2021). MAP is currently diagnosed as a substance induced disorder; however, many researchers suggest that MAP may represent a transition into SSD following substance use (McKetin, 2018). The current study investigated global and local gyrification indices (GI) as a potential neurodevelopmental biomarker for psychosis vulnerability in three quasi-experimental groups; methamphetamine users without psychosis (n=21), individuals with MAP (n=18) and healthy controls (n=21). Gyrification indices were determined for each participant using Freesurfer 7.2 and compared across groups with age and sex as covariates in a multivariate analysis of co-variance (MANCOVA). The results demonstrate that group membership alone significantly accounts for 32% of the variation in overall gyrification (F(12, 106) = 1.87, p=.06, η²=0.16; Wilk's lambda = 0.68, p=.04). Follow-up ANCOVAs suggest that individuals who use methamphetamine have higher temporal gyrification than MAP and control participants, although this result was not statistically significant. There was also a significant effect of age on gyrification (F(6, 50) = 5.37, p<.01, η²=0.39; Wilk's lambda = .61, p<.01). Further associations between gyrification and age (r=-0.43, p<0.05), cannabis use and temporal gyrification (r=0.29, p<0.05), alcohol use and temporal (r=0.34, p<0.05) and parietal gyrification were found (r=0.26, p<0.05), as well as age of methamphetamine use onset (r=-0.40, p<0.05). These results offer more evidence on the harmful effects of drug use on brain structure, posing new questions around the developmental basis of gyrification and its status as a biomarker for disease.